A Good Fight: How Indigenous Women Approach Boxing as a Mechanism for Social Change. (August 2021) - Ross, MacIntosh; Forsyth, Janice
This article examines the experiences of select Indigenous female boxers from Canada and the United States to explore and appreciate the diverse meanings they attach to amateur and professional boxing and to write these athletes into history by constructing short case studies of fighters active from the 1970s through the 2010s. We augment each fighter's story with context from scholarly and secondary source materials, such as newspapers, to round out each woman's story and to illustrate the multiple overlapping conditions that shaped their boxing experiences. We embrace the work of van Ingen on the importance of understanding female boxers at the intersection of race and gender. In doing so, our work emphasizes the ideological foundations embedded in narratives, so that each narrative presents a certain point of view that results in real practical effects, whether it be supporting White liberal feminism or Indigenous self-determination. Following van Ingen, this article views all writing, whether by journalists or professional historians, as ideological acts, capable of exalting select athletes while marginalizing others.